Revealing the Wage Practices of Palm Oil Plantation Laborers From an Islamic Perspective in East Luwu - Yulitasari; Alimuddin; Hasriyodan; Shadra, Yasser Mulla; Andi Riska Andreani Syafaruddin; Thabo Nkosi (Universitas Muhammadiyah Makassar, 2026)
This study aims to reveal the wage practices of palm oil plantation laborers in Kalaena Village, Wotu District, East Luwu Regency, from an Islamic perspective. Using a qualitative method, this research involves in-depth interviews, observations, and documentation studies with laborers, plantation owners, and managers. The results show that the wage system in this area is generally conducted verbally based on mutual agreement and local customs (‘urf), yet fundamental problems persist, such as delayed wage payments, lack of transparency in harvest calculations, and wage imbalances that do not fully consider the level of work difficulty. From an Islamic perspective, wage payment is not merely an economic transaction but constitutes a moral trust that demands the application of the principles of justice (adl), honesty (shidq), appropriateness, and benevolence (ihsan). The findings affirm that the implementation of sharia principles in the wage system remains partial and needs to be improved through written agreements, transparency in wage management, and oversight by relevant institutions. By strengthening Islamic values in wage practices, it is expected that industrial harmony, improved labor welfare, and a wage system that is fair, humane, and aligned with maqashid sharia can be achieved. The recommendations of this study include the need to socialize Islamic business ethics and reform the wage system to be more adaptive to the needs of laborers and local challenges.